Rumah Adat Gebong Memarong: Strategi Hukum dan Ekonomi Dalam Pemanfaatan Ekspresi Budaya Tradisional Sebagai Kekayaan Intelektual Komunal - Nurhayati Dzikri; Muhamad Aziz Zulkifli (Badan Strategi Kebijakan Hukum, 2025)
This study analyzes the forms of legal protection and economic utilization strategies of Rumah Adat Gebong Memarong as a Traditional Cultural Expression (TCE) recognized as Communal Intellectual Property (CIP) in Bangka Belitung. Using a socio-legal research method, this study combines normative legal analysis with an examination of economic policy implementation. The results show that although Gebong Memarong has been officially registered as CIP, its legal protection still faces several obstacles, including limited legal awareness among the Mapur indigenous community, the absence of specific local regulations, and weak digital documentation. These legal and institutional gaps have resulted in the suboptimal economic use of the Gebong Memarong, particularly in developing cultural tourism and creative industries. Therefore, this study proposes integrative strategies that include strengthening community-based institutions, developing creative economy innovations, conducting human resource training, organizing cultural festivals, and promoting digitalization. The study emphasizes that effective legal protection serves as a prerequisite for equitable and sustainable economic development of TCEs. The main contribution of this research lies in formulating an integrative model that bridges legal protection and economic empowerment through a business law perspective. The study contributes theoretically by expanding the discourse on progressive law in protecting communal intellectual property and provides practical implications for local governments in drafting regional regulations (Perda) and designing community-based governance mechanisms for sustainable cultural heritage management.